Pengaturan Wisata Halal Untuk Pembangunan Daerah: Transformasi Industri Halal Di Era Disrupsi - Lukman Santoso; Yutisa Tri Cahyani (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2020)
AbstractHalal tourism is one of the sectors in the global economy that isexperiencing significant development. Indonesia as a country with aMuslim majority has the potential to develop halal tourism. However,there is a regulatory vacuum related to efforts to develop this potential inIndonesia. The existing legal basis is in the form of Fatwa Number 108 /DSN-MUI / X / 2016 concerning Guidelines for Organizing TourismBased on Sharia Principles. The government currently does not have astrong legal umbrella related to the development of the halal tourismsector. This halal tourism potential must be responded positively by theregions through transformative regional regulations as a means of regionaldevelopment and the welfare of the people. This article aims to explorethe ideal transformation model of halal tourism arrangements forsustainable regional development. Using a qualitative-interpretativeapproach, this study produces an ideal and synergic legal model of legalhalal tourism arrangements between local law and Islamic law as aninstrument of regional development in realizing people's welfare in theindustrial revolution era.Keywords: arrangement, transformation, halal tourism, regional regulation